Public administration in Russia as a subject of administrative procedure - Stakhov, A. I.; Landerson, N. V.; Domrachev, D. G. (Pravoprimenenie, 2022)
The subject. Doctrinal approaches that reveal the place and role of public authorities, as well as organizations performing the functions of these authorities in the administrative process carried out in the Russian Federation, the principles and norms of the Constitution of the Russian Federation, administrative procedural legislation that form the legal basis of the administrative process in Russia. The purpose of the article is scientific substantiation of the integration of non-judicial bodies carrying out the administrative procedure into a special subsystem of public power, called public administration in the Russian Federation. The methodology. Formal logical and dialectical methods as well as private scientific methods such as method of interpretation of legal norms, method of comparative jurisprudence were used. The main results, scope of application. The article reveals the scientifically based content of the integrative approach to understanding the administrative process in contemporary Russia, taking into account the norms of the Russian Constitution and the analysis of existing doctrinal developments of administrative scientists. The article substantiates the structure of the administrative procedural legislation of the Russian Federation ant it’s constituent entities, which includes the judicial administrative process and the executive (non-judicial) administrative process implemented by the public administration (executive authorities, local self-government bodies, other administrative and public bodies). Administrativeindicating legal norms are distinguished, the analysis of which allows us to reveal the content, form, structure of the judicial administrative process and the executive (extra-judicial) administrative process, as well as to establish an integrative relationship between them with the help of such special categories as “judicial administrative case”, “extra-judicial administrative case”, “administrative proceedings”, “administrative proceedings”. A number of key proposals are put forward to systematize the judicial administrative process and the executive (extrajudicial) administrative process in Russia on the basis of developed scientific positions. The article reveals the question of a scientifically based theory for understanding the administrative and public functions of public administration, as well as the system and structure of public administration in modern Russia. Conclusions. The presented integrative approach to understanding the administrative process and its differentiated systematization for the judicial administrative process and the executive (non-judicial) administrative process are the only true way to develop the Russian model of administrative process. The question of the need to systematize the administrative and public functions implemented by the public administration is raised. It is proposed to develop and adopt a federal law “On Public Administration in the Russian Federation”, the authors substantiate the content of the structure of this law.